(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2020)
The compulsory portion can be observed from several aspects. Thus, the compulsory portion can be defined from the aspect of the legacy, which is the compulsory portion for the deceased and which is the compulsory portion from the aspect of the compulsory heirs. Legal theory gives us appropriate answers. However, when it comes to the legal nature of the right to a compulsory portion in theory and practice, depending on which facts and reasons are taken for decisiveness, three concepts have emerged: the right on a compulsory portion understood as the hereditary right, the right on a compulsory portion understood as an obligatory right and the right to a compulsory portion understood as a right to provide support. The goal of this paper is first to the extent necessary to study the very notion on right on compulsory portion, and then to carry out scientific elaboration of the legal nature of the right to a compulsory portion, through different conceptions, and on my side I take a position on which conception should be present in our positive inheritance law.